Genetic, environmental and microbiological causes of periodontal diseases - Alhabdan, Yazeed Abdullah; Albeshr, Abdulhameed G.; Alqahtani, Shoroq Mansour; Khallaf, Rudaina Saud; Saidi, Khadijah Mustafa; Alqiraiqri, Khalid Aymen; Aljuaid, Bader Atallah; Albasher, Alaa Abdulkalq; lrasheedi, Naif Mayouf; Altheiaib, Dalal Mohammad; Alsharif, Ahmed Nayef; Alnefaie, Mohammed Abdulrahman (International Journal Of Community Medicine And Public Health, 2021)
Periodontal disease is a term that can be used to describe different oral conditions that occur to the gingiva, in addition to the bones and ligaments supporting the teeth. Periodontal diseases can develop secondary to inflammatory, developmental, genetic, traumatic, neoplastic, and metabolic disorders. In the present literature review, we aim to discuss the different genetic, environmental, and microbiological causes of periodontal diseases based on evidence from the current studies in the literature. Evidence regarding genetics is still not adequate, and further research is still needed to understand the main mechanism of this etiology furtherly. Different diseases and habitual factors can contribute periodontal diseases, mainly due to increased inflammation-induced pathological events. Further attention should be directed to preventing these events to intervene against the development of periodontal diseases adequately. Early interventions against these diseases can attribute to enhance the health and prognosis of the affected patients significantly. Microbiological causes are also important and usually develop mainly as a result of poor hygiene. Therefore, further interventional research should be directed towards raising awareness among individuals to reduce the incidence of the condition.